Insecticide resistance in diamondback moth (Plutella xylostella) (Lepidoptera: Plutellidae) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Plant Health at Massey University - Bell, Peter Daryl (Massey University, 1992)
Diamondback moth is a cosmopolitan species of considerable importance as a pest of cruciferous plants. It is capable of rapid growth in numbers and has a high potential for the development of insecticide resistance. By 1986 resistance had been confirmed to 23 insecticides in 16 countries. A susceptible population was identified from a forage brassica crop on a Massey University farm. Insects collected were used to establish a susceptible laboratory colony. Full dose mortality curves for a range of insecticides were constructed for this colony using leaf dip bioassays. The LD9 values were determined for each of the 7 insecticides tested and used as diagnostic doses to screen field populations for resistance. Field populations regularly exposed to insecticides were sampled at five locations in intensive market garden areas in the North Island. Larvae and pupae collected from these sites were reared to the Fl generation in the laboratory. Third instar larvae were then tested for resistance using leaf dip bioassays treated with the diagnostic doses. Some insecticide resistance was detected at each of the five sites. Insect survival for the site showing the highest resistance levels ranged from 82% to 16% when exposed to the diagnostic dose (LD9 for the susceptible population). Only one site showed resistance to all of the insecticides screened and there seemed to be no pattern to the cross resistance each site. All five sites had spectra encounted on different histories of pesticide usage. Two of the five sites were in close proximity but they were geographically isolated from the remaining 3 sites which were isolated from each other. High levels of parasitism by Diadegma semiclausum was evident in all of the field populations tested. The impact that this is having on the development of resistance is unknown but warrants further study. Even though resistant insects were found, their numbers were low and the crop loss too small to be of concern to the growers. However in the light of experience in South East Asia it would be prudent to formulate resistance management tactics for New Zealand conditions. I suggest that a number of reccomendations should be made to growers with respect to their diamondback moth control programmes. Pyrethroid use should be restricted to one application per brassica crop. The use of control action threasholds should be encouraged as should the use of less persistent insecticides such as dichlorvos and mevinphos. Urgent attention should be given to the development of an efficient grower operated monitoring programme. The feasibility of operating an integrated pest management programme should also be investigated.
Keywords: Plutellidae; Insecticide resistance; Control